The World at the Crossroad. Demographic Polarization and Mass Migration. Global threat or global opportunity - Michele Bruni (Global Labor Organization (GLO), 2019)
The unstoppable progress of the demographic transition is determining a progressive decline of the rates of growth of the total population and working age population of the planet, two phenomena that could have a very positive global socioeconomic and environmental impact. Unfortunately, it is also determining a growing demographic polarization between an increasing number of countries, the most developed ones, where working age population will drop, and a decreasing number, the poorest ones, in which it will explode. The former will be affected by a dramatic structural shortage of labour that will make immigration unavoidable, the latter by a dramatic structural excess of labour that will make emigration necessary to avoid political and socioeconomic havoc. This phenomenon will have extremely disruptive effects not only at the country level but also at the planet level unless both groups of countries will understand that the disease provides its own medicine in the form of well planned and organized migration flows that, while responding to the quantitative and qualitative needs of potential arrival countries, will relieve the poorest countries from their structural excess of labour. Obviously there is a problem: this rational solution is in stark contrast with the myopic and xenophobic vision of an emerging political class that funds its success on the fear of immigrants and fuels xenophobic feelings talking advantage of ignorance and fake news. The incoming demographic polarization does also signal the passage from a situation in which labour markets were affected by economic cyclical disequilibrium to a situation in which they will be affected by a demo-economic structural disequilibrium. This new situation calls for an integrated demo-economic modeling and the use of coordinated sets of demographic and economic measures.
Keywords: J11; J2; J61; 330; migration; labour market; demographic transition; demographic polarization; structural shortage of labour; structural excess of labour